Low Sidelobe Slot Array Antenna Radiating Monopulse Patterns Based on Groove-Transform-Ridge Gap Waveguide - Liang Li; Hongwei Gao; Binchao Zhang; Cheng Jin (International Journal of Antennas and Propagation)
In this paper, a W-band unequal power divider is proposed on the basis of groove-to-ridge gap waveguide, and it is employed to design a low sidelobe level (SLL) slot array antenna with monopulse radiation patterns. The proposed unequal power divider is capable of realizing large power ratio and small phase difference. In light of this property, three different unequal power dividers with various output power ratios and phase balance are proposed for designing a low SLL array antenna. Furthermore, a compare network with planar Magic-Tee is designed for realizing the monopulse radiation patterns. Then, a 32 × 32 antenna array consisting of five unconnected layers is designed, fabricated, and measured. The measured results indicate that the relative impedance bandwidth of the antenna is about 5.5%. In addition, the realized gain of the sum pattern at 84 GHz is 35.4 dBi, while the null of the difference pattern is less than 38 dB. Furthermore, the SLL of the antenna array is more than −25 dB on both the E- and H-planes within the operating band.